Digital soil mapping for precise land management - Moharana, P C; Dharumarajan, S (Indian Farming, 2022)
Digital soil mapping (DSM) has evolved from traditional soil survey to take advantage of advances in computing and geographic data handling, as well as increased availability of environmental covariate data from digital elevation models and remotely sensed imagery. DSM methodology has been adopted by FAO so that digital soil maps can be produced reliably for sustainable land management. DSM has moved from research phase to operational phase across the countries but no fully fledged research has been carried out in India. ICAR-National Bureau of Soil Survey and Land Use Planning (ICAR-NBSS&LUP), Nagpur has recently worked on Digital soil mapping with the objective to develop soil properties map as per GlobalSoilMap Specifications. DSM will be regarded as key for guiding decision-makers in natural resource assessment, environmental modeling, and land use studies.